Ophthalmological aspects of coronavirus infections - V. V. Neroev; T. N. Kiseleva; E. K. Eliseeva (Российский офтальмологический журнал, 2021)
The novel coronavirus infection (COVID-19) caused by SARS-CоV-2 virus, may lead to ocular diseases besides affecting the respiratory system. Cororonavirus infection may be transmitted not only through the respiratory system but also through the conjunctiva. The review article summarizes the data on the origin and variants of coronaviruses that infect humans, as well as on SARS-CоV-2 structures. Literature data on prospects of molecular diagnostics of the disease, coronavirus type detection methods, clinical sample types and duration of the disease before it is diagnosed are discussed. The data on the relationship between the coronavirus infection and conjunctivitis are given. Molecular tests of the tear and conjunctival swabs were used to diagnose the coronavirus infection independently of whether symptoms of ocular disorders were present. The real-time reverse-transcription of RNA polymerase chain reaction (PCR) was the most informative method for diagnosis of SARS-CоV-2 in the early stage of COVID-19 (until the 9th day). The presence of SARS-CоV-2 in the tear fluid and conjunctival swabs indicates the need for safety measures to prevent virus transmission through the ocular surface, including protective goggles to be worn by healthcare workers. Since side effects in the eye may appear, COVID-19 patients with visual impairment who received etiotropic or pathogenetic treatment are advised to consult an ophthalmologist.